2016
DOI: 10.1080/10410236.2016.1219931
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Resistance to Narrative Persuasion About Binge Drinking: The Role of Self-Activation and Habitual Drinking Behavior

Abstract: This study explores the effects of habitual health risk behaviors and self-activation on resistance to narrative persuasion. In two experiments, heavier drinkers were more resistant to an anti-binge-drinking narrative public service announcement (PSA) in which a binge drinker suffers a negative outcome. Specifically, heavier drinkers were more likely to generate counterarguments, unrealism judgments, and negative evaluations about the message compared to lighter drinkers or nondrinkers. However, activating sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 78 publications
0
10
0
1
Order By: Relevance
“…Self-activation occurs when a narrative depicts experiences that are directly relatable to an audience, allowing them to perceive the actions as happening to themselves, rather than perceiving events from the character's perspective. (Zhou andShapiro, 2017, p. 1298). Self-activation gives the narrative more credibility and evoking thoughts consistent with the narrative's message (Zhou andShapiro, 2017, p. 1298).…”
Section: Character Identification and Self-activationmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-activation occurs when a narrative depicts experiences that are directly relatable to an audience, allowing them to perceive the actions as happening to themselves, rather than perceiving events from the character's perspective. (Zhou andShapiro, 2017, p. 1298). Self-activation gives the narrative more credibility and evoking thoughts consistent with the narrative's message (Zhou andShapiro, 2017, p. 1298).…”
Section: Character Identification and Self-activationmentioning
confidence: 99%
“…Self-activation gives the narrative more credibility and evoking thoughts consistent with the narrative's message (Zhou andShapiro, 2017, p. 1298). People can become acutely aware of selfrelated consciousness, including knowledge of a specific issue and/or personal associations related to that issue (Zhou andShapiro, 2017, p. 1298). Zhou and Shapiro (2017) found that this perspective was useful for narratives targeting people engaging in binge drinking.…”
Section: Character Identification and Self-activationmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, research on the impact of narratives on health has received special attention in recent years, in issues such as organ donation (for example: Appel & Richter, 2010), over-the-counter drug use (Kim (Dunlop, Wakefield, & Kashima, 2010), alcohol consumption (Gebbers, Wit & Appel, 2017;Moyer-Gusé, Jain & Chung, 2012;Zhou & Shapiro, 2017) and HPV prevention (for example: Murphy et al, 2013;Nan, Futerfas & Ma, 2017), among others.…”
Section: Narrative Persuasion In Healthmentioning
confidence: 99%
“…De hecho, la investigación sobre el impacto de las narrativas en salud ha recibido especial atención en los últimos años, en temas como la donación de órganos (por ejemplo, (Appel & Richter, 2010), el consumo de medicamentos sin prescripción (Kim & Shapiro, 2016), el uso de protección solar (Dunlop, Wakefield, & Kashima, 2010), el consumo de alcohol (Gebbers, Wit, & Appel, 2017;Moyer-Gusé, Jain, & Chung, 2012;Zhou & Shapiro, 2017), la prevención del virus del papiloma humano (por ejemplo, Murphy et al, 2013;Nan, Futerfas, & Ma, 2017), entre otros.…”
Section: Persuasión Narrativa En Saludunclassified